Active vibration control of CNT-reinforced composite cylindrical shells via piezoelectric patches. (15th December 2016) - Song, Z.G.; Zhang, L.W.; Liew, K.M.
Abstract: The active vibration control of carbon nanotube (CNT) reinforced functionally graded composite cylindrical shell is studied in this investigation using piezoelectric materials. Piezoelectric patches are bonded onto the outer and inner surfaces of the cylindrical shell to act as the actuator and sensor, respectively. Thermal effects are taken into account. Reddy's high-order shear deformation theory is used in the structural modeling. The displacement fields of the piezoelectric actuator and sensor are given, according to the geometrical deformation relationship. The equation of motion of the CNT reinforced composite cylindrical shell is formulated by way of Hamilton's principle, the solution of which is derived using the assumed mode method. In the research surrounding active vibration control, the controller is designed using velocity feedback and LQR methods. Influences of thickness on the vibration control effects of the cylindrical shell are analyzed. The control results gained by way of different control methods are compared. The active control effects of cylindrical shells with different placements of piezoelectric patches are also researched.